Pralsetinib treatment for multiple RET fusions in lung adenocarcinoma: a case report. Issue 6 (June 2022) - Cao, Xiangming; Liu, Xiongwei; Wang, Simin; Liu, Zhen; Ren, Xin; Sun, Debin; Deng, Lichun
Despite recent advances in treatments and knowledge of biomarkers, patients with metastatic lung cancer have a 5-year survival rate of 5%. Rearranged during transfection ( RET ) fusions occur in 1% to 2% of lung cancer patients. Pralsetinib has been used to treat non-small cell lung cancer with a single RET fusion; however, there have been no reports regarding its use in patients with multiple RET fusions. Genetic mutations in tumor tissues were tested using Amplification Refractory Mutation System-PCR and next-generation sequencing (NGS). Pleural fluids obtained from a male patient with non-small cell lung cancer were also used to detect genetic aberrations by NGS. Pleural fluid-based NGS revealed three RET rearrangements: CCDC6 - RET (C2:R12), RET - NRG3 (R11:N3), and CCDC6 - RET (C1:R12). All three rearrangements were targeted by pralsetinib, a RET fusion inhibitor. Pralsetinib drastically improved the patient's condition within 4 days, and a partial response was achieved 1 week after pralsetinib was administered. We report for the first time the important clinical observation of a patient with multiple RET fusions who was effectively treated with pralsetinib.